Revealing the non- phytotoxic effect of gunapaselam (fermented fish waste) by a dose dependent in vitro study - B. THENDRAL HEPSIBHA; A. GEETHA (International Journal of Pharma and Bio Sciences, 2017)
Disposal of fish waste without proper treatment creates an environmental nuisance. Fish waste like head, fins, viscera etc., were collected and degraded by natural fermentation with jaggery. The present study reports the nontoxic nature of fermented fish waste (Gunapaselam) on germination and growth promoting property on Vigna radiata at different concentrations (25, 50, 75 and 100 fold dilutions) by Petri plate in vitro model. Treatment of green gram seeds with Gunapaselam shows that at dilutions from 50 fold onwards fermented fish waste was able to promote the formation of leaf, shoot, tap root and secondary roots. There is a significant improvement in the concentration of plant pigments (Chlorophyll, carotenoids and xanthophylls) and protein content. This study suggests that the fish waste can be used as fertilizer after diluting the fermented liquid.